When digital becomes human : the transformation of customer relationships - Van Belleghem, Steven (Kogan Page, 2015)
"In an age when customers have access to vast amounts of data about a company, its product and its competitors, customer experience becomes increasingly important as a sustainable source of competitive advantage. In a recent global market study, 73% of respondents stated that even when a company's digital channels work perfectly, they still want access to a real person. Steven Van Belleghem explores and explains the new digital relationships and offers a strategic guide to combining a business's two most important assets -- its people and its digital strengths. He shows marketing managers, directors and commercial decision makers how to positively transform customers' digital experiences by adding a human touch. He covers the latest issues in digital marketing and CRM including: omnichannel and multichannel experiences, big data and predictive analytics, privacy concerns, and crowdsourcing. Packed with examples from organizations that have successfully transformed their customer relationships, such as Amazon, Toyota, ING, Nike and Starbucks, the book presents a clear model that illustrates how to integrate an "emotional" layer in any digital strategy to achieve consumer engagement and loyalty"--